Mitochondrial Dysfunction in Astrocytes: A Role in Parkinson’s Disease? - Bantle, Collin M.; Hirst, Warren D.; Weihofen, Andreas; Shlevkov, Evgeny (Frontiers in Cell and Developmental Biology, 2021)
Mitochondrial dysfunction is a hallmark of Parkinson’s disease (PD). Astrocytes are the most abundant glial cell type in the brain and are thought to play a pivotal role in the progression of PD. Emerging evidence suggests that many astrocytic functions, including glutamate metabolism, Ca2+ signaling, fatty acid metabolism, antioxidant production, and inflammation are dependent on healthy mitochondria. Here we review how mitochondrial dysfunction impacts astrocytes, highlight translational gaps, and open new questions for therapeutic development.